An Introduction to Shared-Use Commercial Kitchens - Matthew Krug; Sarah M. Ellis (EDIS)
Shared-use commercial kitchens are commonly used by food entrepreneurs to launch new food products into market; however, there remain questions about how these facilities work. This new 4-page document defines basic terms used to describe shared-use commercial kitchens, such as incubator, accelerator, or food hub, and gives an overview of potential services or resources available at these facilities. Furthermore, basic information on state level food regulations and an extensive list of Shared-use Commercial Kitchens in Florida is included. Written by Matthew Krug and Sarah Ellis and published by the UF/IFAS Food Science and Human Nutrition Department. https://edis.ifas.ufl.edu/fs400